Development of elasto-plastic viscous damper finite element model for reinforced concrete frames - Hejazi, Farzad; Zabihi, Alireza; Jaafar, Mohd Saleh (Elsevier, 2014)
By advancing the technologies regarding seismic control of structures and development of earthquake resistance systems in the past decades application of different types of earthquake energy dissipation system has incredibly increased. Viscous damper device as a famous and the simplest earthquake energy dissipation system is implemented in many new structures and numerous number of researches have been done on the performance of viscous dampers in structures subjected to earthquake. The experience of recent severe earthquakes indicates that sometimes the earthquake energy dissipation devices are damaged during earthquakes and there is no function for structural control system. So, damage of earthquake energy dissipation systems such as viscous damper device must be considered during design of earthquake resistance structures. This paper demonstrates the development of three-dimensional elasto-plastic viscous damper element consisting of elastic damper in the middle part and two plastic hinges at both ends of the element which are compatible with the constitutive model to reinforce concrete structures and are capable to detect failure and damage in viscous damper device connections during earthquake excitation. The finite element model consists of reinforced concrete frame element and viscous damper element is developed and special finite element algorithm using Newmark׳s direct step-by-step integration is developed for inelastic dynamic analysis of structure with supplementary elasto-plastic viscous damper element. So based on all the developed components an especial finite computer program has been codified for “Nonlinear Analysis of Reinforced Concrete Buildings with Earthquake Energy Dissipation System”. The evaluation of seismic response of structure and damage detection in structural members and damper device was carried out by 3D modeling, of 3 story reinforced concrete frame building under earthquake multi-support excitation.